Quotient Rule of Exponents :
When dividing exponential expression that have the same base, subtract the exponents.
Example 1 :
Solution :
Example 2 :
Solution :
Example 3 :
Solution :
Example 4 :
Solution :
Example 5 :
Solution :
Example 6 :
Solution :
Example 7 :
Solution :
Example 8 :
6x5 ⋅ 3x5 ⋅ x0
Solution :
Multiply the coefficients,
= 6x5 ⋅ 3x5 ⋅ x0
= (6 × 3)(x5 ⋅ x5 ⋅ x0)
By am ⋅ an = am+n,
= 18(x5+5 ⋅ x0)
= 18(x10⋅ x0)
= 18x10
Example 9 :
(3st12)3
Solution :
= (3st12)3
= 33s3(t12)3
= 27s3(t12)3
By (am)n = amn,
= 27s3t(12×3)
= 27s3t36
Example 10 :
Solution :
Example 11 :
Solution :
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM